Descriptive analysis of central line-associated bloodstream infections in a pediatric hematology–oncology unit in Montevideo, Uruguay - Morosini, Fabiana; Silveira, Anaulina; Irigoyen, Beatriz; Homsi, Maysam R.; Castillo, Luis; Caniza, Miguela A. (International Journal of Infection Control, 2022)
Background: Central lines are essential for the care of children with cancer. Aims: To determine the risk factors, characteristics, cost of hospital care, and antibiotic use in pediatric oncology patients with central line-associated bloodstream infections (CLABSIs). Methods: During 2018–2019, we calculated the rate of CLABSIs in our pediatric hematology–oncology unit. Findings: Between 2018 and 2019, we detected 34 CLABSIs at our pediatric hematology–oncology unit. We identified neutropenia as the main risk factor for CLABSI (3.74 infections per 1,000 catheter days vs. 1.15 infections per 1,000 catheter days in patients without neutropenia). Three patients died of septic shock. Escherichia coli, Klebsiella species, and Pseudomonas species were frequently isolated. The total healthcare cost of the 34 CLABSIs was more than US$1.2 million. Conclusions: CLABSI is an avoidable disease among children with cancer. Investing in CLABSI prevention will save lives and financial resources of the hospital. Preventive measures, surveillance, and reporting the rate of CLABSIs are essential for quality assurance and patient safety during cancer-directed treatment of children.